Could exposure to phthalates speed up or delay pubertal onset and development? A 1.5-year follow-up of a school-based population. (October 2015) - Zhang, Yunhui; Cao, Yang; Shi, Huijing; Jiang, Xiaoxiao; Zhao, Yan; Fang, Xin; Xie, Changming
Abstract: Purpose: Phthalates may interfere with the timing of pubertal development in adolescence and existing studies have shown inconsistent results. This study aims to assess the associations of pubertal onset and progression with urinary concentrations of phthalate metabolites in school-aged boys and girls. Methods: Using isotope-dilution liquid chromatography tandem mass spectrometry, we analyzed 6 phthalate metabolites in urine samples of 430 children (222 boys and 208 girls) aged 9.7 ± 2.2 years (age range 6.1 to 13.8 years) at baseline and 18 months of follow-up. The associations of exposures to phthalates with pubertal development such as the testis, breast and pubic hair were evaluated using ordered logistic regression models, adjusting for baseline development stage, current chronological age, current body fat composition, and parental education. Results: Urinary mono-n-butyl phthalate (MnBP) was associated with a 39% increase in the odds of presenting lower pubic hair development stages in boys, and mono (2-ethylhexyl) phthalate (MEHP) (p < 0.10), mono (2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) and mono (2-ethyl-5-oxohexyl) phthalate (MEOHP) were associated with 54%–65% increase in the odds of presenting higher breast development stages in girls (p < 0.05), while MEHHP and MEOHP were also associated with a 70% increase in the odds of menarche onset (p < 0.05). After adjusting for potential confounding variables, the associations of girls' pubertal onset with MnBP, MMP, MEP and MEHP were significant. The odds of girls' breast onset were 4 to 10 times higher in high MnBP, MMP, MEP or MEHP exposure group than in low exposure group. Conclusions: Our findings suggest subtle effects of phthalate metabolites associated with pubertal onset and progression. MnBP exposure may be associated with delayed pubic hair development in boys, while MnBP, MMP, MEP, and MEHP exposures may be associated with breast onset, and MEHP metabolites associated with speedup in breast development progression and earlier menarche onset in girls. Highlights: We examine associations of pubertal onset and progression with phthalate exposure. Urinary concentrations of six phthalate metabolites are analyzed. MnBP exposure is associated with delayed pubic hair development in boys. MnBP, MMP, MEP, and MEHP exposures are associated with breast onset in girls. MEHP metabolites are related to speedup in breast progression and earlier menarche.